Knowledge, attitude and practices on secondhand smoking among women who are exposed to secondhand smoking at home and at workplace - Ismail, Suriani; Mohd Zulkefli, Nor Afiah; Mahmud, Aidalina; Abu Bakar Al Sidek, Nurul Diyana; Ramalingam, Dhevann Raj (Community Health Society Malaysia, 2017)
Introduction: Second-hand smoking (SHS) is involuntary smoking of exhaled smoke from smokers. SHS is dangerous to health as there is no safe level of exposure. Knowledge, attitude and practice towards SHS are important prevention measures especially among working women whose husbands are smokers. Methods: A cross-sectional study was conducted among staff members of a public university. Respondents were the wives of smokers and recruited using simple random sampling. Data was collected using a self-administered questionnaire. Chi-square test was used to determine the associations between variables. Results: Majority (66.2%) of the respondents have appropriate practices towards SHS and there was no significant differences within the socio-demographic characteristics. Correspondingly, 53.7% have good knowledge but only 46.3% have good attitude towards SHS and 74.6% showed lack of confidence in reprimanding smokers in no-smoking zone. Conclusion: The appropriate practices towards SHS among the wives of smokers in this study was good. However the self-efficacy to avoid SHS could be improved.